Resonant Hall effect under generation of a self-sustaining mode of spin current in nonmagnetic bipolar conductors with identical characters between holes and electrons. (8th February 2018) - Sakai, Masamichi; Takao, Hiraku; Matsunaga, Tomoyoshi; Nishimagi, Makoto; Iizasa, Keitaro; Sakuraba, Takahito; Higuchi, Koji; Kitajima, Akira; Hasegawa, Shigehiko; Nakamura, Osamu; Kurokawa, Yuichiro; Awano, Hiroyuki
Abstract: We have proposed an enhancement mechanism of the Hall effect, the signal of which is amplified due to the generation of a sustaining mode of spin current. Our analytic derivations of the Hall resistivity revealed the conditions indispensable for the observation of the effect: (i) the presence of the transverse component of an effective electric field due to spin splitting in chemical potential in addition to the longitudinal component; (ii) the simultaneous presence of holes and electrons each having approximately the same characteristics; (iii) spin-polarized current injection from magnetized electrodes; (iv) the boundary condition for the transverse current ( J c, y = 0). The model proposed in this study was experimentally verified by using van der Pauw-type Hall devices consisting of the nonmagnetic bipolar conductor YH x ( x ≃ 2) and TbFeCo electrodes. Replacing Au electrodes with TbFeCo electrodes alters the Hall resistivity from the ordinary Hall effect to the anomalous Hall-like effect with an enhancement factor of approximately 50 at 4 T. We interpreted the enhancement phenomenon in terms of the present model.